Peripheral EMG comparison between fully tethered and free front crawl swimming - Bollens, E.; Annemans, L.; Vaes, W.; Clarys, J. P. (Swimming Science V, 1988)
Front crawl swimming has been a subject of several electromyographic (EMG) investigations. The main purpose of these studies was to make statements on muscular action in normal front crawl swimming. This resulted in normalized EMG patterns for up to 25 superficial muscles involved in front crawl swimming (Oarys, 1983; Clarys, Massez, Van Den Broeck, Piette, & Robeaux, 1983; Lewillie, 1974; Maes, Oarys, & Brouwer, 1975) and in the development of a sophisticated data-recording system (Clarys & Publie, 1987). With this knowledge and the technical knowledge of surface EMG registration in water, EMG research in swimming focused on the specificity of some alternative training methods (i.e., comparing muscular activity in one or another test protocol with muscular activity in normal front crawl swimming). Dryland devices such as the isokinetic swim bench, roller board, expander, and call craft did not give satisfactory results. The main problem in dryland training was the elimination of the equilibrium mechanisms that are present in normal swimming (Olbrecht & Clarys, 1983). In an attempt to eliminate the influence of these mechanisms, we investigated the influence of six different types of hand paddles on the muscular activity during swimming the front crawl. This study showed that hand paddle swimming is muscle-specific with normal front crawl swimming although not unconditionally the same (Bollens & Clarys, 1984). Although tethered swimming, another alternative swimming method, has been the subject of a number of scientific studies, none of these investigations were concerned with the muscular specificity aspects of this training method (Cureton, 1930; Mosterd & Jongbloed, 1964; Van Manen & Rijken, 1975; Zatsiorsky & Safarian, 1972). The present study dealt vvith verifying similarities or differences in muscular activity between normal (free) front crawl swimming and fully tethered swmming.